2019
DOI: 10.1007/s10644-019-09257-5
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationship between finance, institutions and economic growth: evidence from the ASEAN economies

Abstract: This study investigates the role of financial and institutional development on economic growth in the Association of Southeast Asian Nations (ASEAN) economies from 1995 to 2017 using a dynamic panel estimator. Financial development is instrumental in promoting economic growth; however, the effect of financial institutions and financial markets can differ. In recent years, the ASEAN economies have launched financial and institutional integration initiatives towards the goal of an integrated ASEAN Economic Commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 83 publications
6
51
0
1
Order By: Relevance
“…Finally, rule of law is positive and statistically significant for financial development as measured by both Private sector domestic credit to GDP ratio and Broad Money Supply to GDP ratio highlighting the importance of better quality institutions for financial development consistent with the arguments of Haini (2019) and Marcelin and Mathur (2014) the improved institutions may promote financial development for instance through curbing systemic risk and hence reducing financing costs.…”
Section: Panel Data Fixed Effects Instrumental Variables Second Stage Regression For Determination Of Financial Development In West Africsupporting
confidence: 53%
“…Finally, rule of law is positive and statistically significant for financial development as measured by both Private sector domestic credit to GDP ratio and Broad Money Supply to GDP ratio highlighting the importance of better quality institutions for financial development consistent with the arguments of Haini (2019) and Marcelin and Mathur (2014) the improved institutions may promote financial development for instance through curbing systemic risk and hence reducing financing costs.…”
Section: Panel Data Fixed Effects Instrumental Variables Second Stage Regression For Determination Of Financial Development In West Africsupporting
confidence: 53%
“…According to Haini (2019), financial markets development are enhancing economic growth in Southeast Asia. As the Islamic financial markets of Sukuk (Islamic bonds) are part of the financial markets and for the reason that Sukuk markets enhance economic growth internationally, this paper formulates the hypothesis as the following: H1.…”
Section: Prrmentioning
confidence: 99%
“…Economic growth is an important issue concerned by scholars all over the world. Onifade S T(2020) found that there is a long-term correlation between public expenditure and economic growth, government expenditure has a negative impact on economic growth, and public expenditure and domestic investment are the Granger causes of economic growth [1]; Hasan M A(2019) found that economic globalization and political globalization accelerate economic growth in the long run, but the impact of shortage is not obvious [2]; Haini H(2020) the empirical results show that financial institutions have a significant positive impact on economic growth, but the impact of financial market is not obvious [3]; Kalaitzi A(2020) found that export will increase investment in sectors with comparative advantages, thus increasing economic growth rate. At the same time, export will increase foreign exchange inflow, which will also stimulate economic growth [4]; Gani A(2020) found that China's economic growth has a significant positive impact on Africa, while India's economic impact is not significant [5]; Qamruzzaman, M.(2018) found that financial innovation and economic growth have long-term cointegration.…”
Section: Literature Reviewmentioning
confidence: 99%